Effects of the roots of Cynodon dactylon and Schefflera heptaphylla on water infiltration rate and soil hydraulic conductivity - Leung, A. K.; Garg, A.; Coo, J. L.; Ng, C. W. W.; Hau, B. C. H. (Hydrological processes, 2015)
Water infiltration rate and hydraulic conductivity in vegetated soil are two vital hydrological parameters for agriculturists to determine availability of soil moisture for assessing crop growths and yields, and also for engineers to carry out stability calculations of vegetated slopes. However, any effects of roots on these two parameters are not well‐understood. This study aims to quantify the effects of a grass species, Cynodon dactylon, and a tree species, Schefflera heptaphylla, on infiltration rate and hydraulic conductivity in relation to their root characteristics and suction responses. The two selected species are commonly used for ecological restoration and rehabilitation in many parts of the world and South China, respectively. A series of in‐situ double‐ring infiltration tests was conducted during a wet summer, while the responses of soil suction were monitored by tensiometers. When compared to bare soil, the vegetated soil has lower infiltration rate and hydraulic conductivity. This results in at least 50% higher suction retained in the vegetated soil. It is revealed that the effects of root‐water uptake by the selected species on suction were insignificant because of the small evapotranspiration (<0.2 mm) when the tests were conducted under the wet climate. There appears to have no significant difference (less than 10%) of infiltration rates, hydraulic conductivity and suction retained between the grass‐covered and the tree‐covered soil. However, the grass and tree species having deeper root depth and greater Root Area Index (RAI) retained higher suction. Copyright © 2015 John Wiley & Sons, Ltd.